Websockets Shared Virtual Whiteboard; an alternative for remote collaborative work - Sotomayor, Xavier; Ordóñez Camacho, Diego (Enfoque UTE, 2017)
The Websockets Shared Virtual Whiteboard, is a system for cooperative work, that allows its users to collaborate remotely, online and in real time. The system provides with a virtual whiteboard acting as a shared workspace where any user´s interactions synchronize automatically and immediately with all the other users. Server side, the system is implemented with the Java Enterprise Edition, mainly using WebSockets technology. Client side, no installing process is necessary, given that any recent browser supporting WebSockets through Javascript, whether on desktop or mobile systems, is able to integrate itself into a working session. The chosen configuration allows the users to hand-draw, and use geometric figures and text boxes; it is possible to save any stage of the working environment to file and reload it for a different session; moreover, a chat tool has been incorporated, which provides with a complementary workspace for adding contextual explanations to the session, everything in a collaborative environment.